High performance indium tin oxide-free solution-processed organic light emitting diodes based on inkjet-printed fine silver grid lines - Hermerschmidt, Felix; Burgués-Ceballos, Ignasi; Savva, Achilleas; Sepos, Eleftherios D.; Lange, Alexander; Boeffel, Christine; Nau, Sebastian; List-Kratochvil, Emil J. W.; Choulis, Stelios A. (My University, 2016)
Wereport on the grid design requirements and inkjet-printing processing conditions of well-defined silver nanoparticles combined with poly(3, 4-ethylenedioxylthiophene):poly(styrenesulfonate) PEDOT:PSS as indium tin oxide (ITO) replacement for ITO-free organic light emitting diodes (OLEDs). Solution-processed ITO-free OLEDs based on the 5BTF8 blend of poly(9, 9-dioctylfluorene-alt-benzothiadiazole(F8BT) and poly(9, 9-di-n-octylfluorenyl-2, 7-diyl) (PFO) light-emitting layers, processed in ambient conditions, showed comparable luminance efficiency and power efficiency values to reference devices based on ITO and near identical efficiencies at low luminance values.
Keywords: Inkjet printing; ITO-free electrodes; Organic light emitting diodes; Printed electronics Supplementary material for this article is available online; Silver nanoparticle grids